The Influence of Work Motivation, Job Rotation and Career Development on Employee Performance - Dewa, Adenanthera (LifeSciFi, 2021)
The Kijang Port in Riau, marked by heavy congestion and high traffic density in sea transportation, operates in an era of fierce competition, not only from domestic but also international competitors due to the influence of free trade. In this context, businesses strive to enhance their resource utilization efficiency to secure a competitive edge. Notably, employee performance stands at the core of organizational success, significantly affected by various factors, including work motivation, job rotation, and career development. This study explores these elements and their impact on employee performance at the Kijang Port. The findings of the research showcase work motivation as the most influential factor in driving employee performance, supported by its positive and significant relationship. Job rotation and career development also exhibit positive and significant effects on employee performance, although they rank below work motivation in terms of influence. The study recommends that organizations and management at the Kijang Port prioritize strategies for enhancing work motivation among employees and consider approaches to promote job rotation and facilitate career development. Addressing these factors has the potential to lead to improved overall performance and productivity, underscoring the importance of fostering work motivation, job rotation, and career development as strategies for optimizing employee performance at the Kijang Port, Riau Islands.